2008
DOI: 10.1002/lsm.20627
|View full text |Cite
|
Sign up to set email alerts
|

Scattered UV irradiation during VISX excimer laser keratorefractive surgery

Abstract: The scattered actinic UV laser radiation from the VISX Star S3 excimer laser did not exceed occupational exposure limits during a busy 8-hour workday, provided that operating room personnel were at least 80 cm from the treated eye. While the use of protective eyewear is always prudent, this study demonstrates that the trace amounts of scattered laser emissions produced by this laser do not pose a serious health risk even without the use of protective eyewear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Measurements were corrected by multiplying by a factor of 1.2 to adjust for the reduced sensitivity of the detector at a 193 nm wavelength. Although the manufacturer suggests an error correction of 5%, the study followed previous investigations 7, 8 and used a more conservative safety factor for uncertainty. The detector aperture on the photodiode head measures 0.7854 cm 2 , and few pulses of the total scattered UV radiation hit the detector head.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were corrected by multiplying by a factor of 1.2 to adjust for the reduced sensitivity of the detector at a 193 nm wavelength. Although the manufacturer suggests an error correction of 5%, the study followed previous investigations 7, 8 and used a more conservative safety factor for uncertainty. The detector aperture on the photodiode head measures 0.7854 cm 2 , and few pulses of the total scattered UV radiation hit the detector head.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of UV scatter with LADARVision and VISX lasers 7,8 found that emissions did not exceed the maximum permissible exposure for health care workers during refractive surgery. The purpose of this study was to evaluate the potential occupational hazards from exposure to scattered UV radiation from a newer high-frequency, wavefront-optimized excimer laser platform in a typical operating room environment.…”
mentioning
confidence: 98%